PERFORMANCE EVALUATION ANALYSIS OF THE FAMILY PLANNING EXTENSION TEAM IN REDUCING THE STUNTING LEVEL AT THE P5A SERVICE GUNUNGSITOLI CITY - Martalena Mendrofa; Odaligoziduhu Halawa; Yamolala Zega; Palindungan Lahagu (LPPM YPITI, 2026)
This study aims to analyze the performance evaluation of the Family Planning extension team at the Population Control, Women's Empowerment, and Child Protection Office of Gunungsitoli City in efforts to reduce stunting rates. The approach used was a descriptive qualitative approach, with data collection techniques through in-depth interviews, participant observation, and documentation studies. Research informants were selected purposively, including family planning extension workers, structural officials of the P5A Office, and community beneficiaries of the program. The research results indicate that the performance of the family planning extension team was generally effective and adaptive. This is reflected in a periodic quantitative and qualitative evaluation system, solid cross-agency coordination, and ongoing training that enhances the extension workers' capacity as agents of change. The educational strategy employed was interpersonal and contextual, with a participatory, demonstrative, and collaborative approach with local leaders and female cadres. This strategy successfully increased nutrition awareness, healthy lifestyles, and community participation in integrated health service posts (Posyandu) and maternal and child health services. However, program implementation faces various challenges, including limited number of extension workers, geographical barriers, socio-cultural resistance to family planning programs, and a lack of technology-based educational media. Supporting factors such as institutional commitment, cross-sector synergy, and community trust are key strengths in strengthening community-based interventions. This study concludes that successful stunting reduction depends heavily on the quality of interactions between extension workers and the community, as well as ongoing institutional support. Therefore, innovative communication strategies and strengthening institutional capacity are needed to ensure the program's overall sustainability.